Early Mobilization Accelerates Gastrointestinal Function Recovery in Postoperative Cesarean Section Patients - Indriati, Ratna; Rosalinna, Rosalinna; Paryono, Paryono (Jurnal Kebidanan dan Kesehatan Tradisional, 2024)
Background: Early mobilization is an important intervention for post-cesarean section patients as it can accelerate flatus time and reduce gas accumulation in the digestive organs. This effort also helps prevent post-operative complications such as gastrointestinal disorders, circulatory disorders, and abdominal distension through increased gastrointestinal muscle tone and stimulation of intestinal peristalsis. The purpose of this study was to determine the effect of early mobilization on normal digestive function in post-cesarean section patients in the Drupadi Room of Bagas Waras Klaten Regional General Hospital.  Methods: This study used a quasi-experimental design with a post-test only with control group. The study was conducted in November 2022 in the Drupadi Room of Bagas Waras Klaten Regional General Hospital. The sample consisted of 40 post-cesarean section mothers selected using purposive sampling. The research instrument was a flatus time observation sheet. Data analysis was performed using an independent t-test to determine the difference in digestive function between the early mobilization group and the control group.  Results: The results showed a significant difference between the early mobilization group and the control group in terms of flatus time (p-value <0.001). The average flatus time in the early mobilization group was 206.40 minutes, while in the control group it was 485.75 minutes.  Conclusion: Early mobilization has a significant effect on accelerating normal digestive function in patients after cesarean section. Midwives can optimize the implementation of early mobilization as part of standard post-cesarean section care to accelerate gastrointestinal function recovery.